(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
Stoma formation is a procedure commonly performed in colorectal surgery as part of operations performed for inflammatory and malignant bowel disease. Stoma formation is a simple but not trivial task. When done poorly, it can leave patients with a legacy of complications such as leakage, prolapse, parastomal hernia, and retraction. Objective: To determine the factors associated with complications in patients with intestinal ostomies in the emergency area of the "Abel Gilbert Pontón" Hospital during 2019. Methodology: Study of a non-experimental, observational, analytical, retrospective and cross-sectional type, which analyzed patients with intestinal ostomies who presented postoperative complications at the Abel Gilbert Pontón Hospital. Results: The frequency of postoperative complications was 42.5% (n = 20), the female gender predominated in the group with complications, without statistical significance (Group A: 59.3% vs. Group B: 65%). The most frequent age group between the two groups was 56 to 75 years. The greater etiology of both groups was due to acute absences not related to trauma (Group A 96% vs. Group B 90%) and the colon was the most affected organ in the surgeries performed with a greater presentation in Group B without statistical significance ( Group A 52% vs. Group B 70%).